The Route 9 Anthology : A Collection of Writing from Wesleyan Students, Faculty, Staff & Middlesex County Residents - Egger, Oliver; Egger, Oliver (Book collections on Project MUSE., 2022)
A collection of writing from across Wesleyan University and its surrounding towns. The Route Nine Anthology is a collection of poetry and prose from Wesleyan students, faculty, staff, and Middlesex County residents. It is the first collection of prose dedicated specifically to bridging the literary divide between the Wesleyan and Middlesex County communities.